Medhātithi Gautama Pendiri Ānvīkṣikī Par Excellence : Relevansinya dengan Bidang Baru Penelitian Filsafat Hindu di Indonesia - Ni Kadek Surpi; Krisna S Yogiswari (Jurnal Penelitian Agama Hindu, 2021)
Medhātithi Gautama is the Founder of Ānvīkṣikī par excellence. Gautama is believed to have written the Nyāya-Sūtra (Rules of Logic) in 550 BC, which are considered the earliest writings of the Indian system of logic. Ānvīkṣikī is the science of critical study, reasoning, and debate that has developed since ancient times in the building of Vedic knowledge. Ānvīkṣikī as a light of knowledge, support for dharma, and even as a means of liberation. Medhātithi Gautama has constructed Indian logic's structure, inherited and developed by later thinkers, with many written works. Today, Ānvīkṣikī's knowledge can be traced to the writings of Mahamahopadhyaya Satis Chandra Vidyabhusana (1920) and other writers, albeit in limited numbers. While in Indonesian, this article is a pioneer of Medhātithi Gautama's work and thoughts in Hindu logic. This article is a text study, using content analysis, providing new interpretations and meanings. The author integrates his text research style with new techniques in Hindu writing from Mīmāṃsā to Navya-Nyāya styles to obtain fresh and new perspectives and thoughts. This study shows that Ānvīkṣikī is a significant subject in Hindu philosophy and has the potential to become a new field of research in the realm of philosophy in Indonesia. The limited access to reading sources and research results in Indonesia seem to make the study of Hindu philosophy have not experienced much development in recent years. Therefore, efforts are needed to study classical texts and teachings so that they can be written and interpreted to be used as a basis for learning various sub-fields of philosophy. Besides, learning Ānvīkṣikī will strengthen reasoning power, critical thinking skills, debate, and discussion. This ability seems very important to be developed to strengthen the position of Hindu scholarship and build a group of Jñānī (scientists, thinkers, writers, One who pursues the path of jñāna, or knowledge) in the Hindu community.